Esophageal contractile segment impedance from high-resolution impedance manometry correlates with mean nocturnal baseline impedance and acid exposure time from 24-hour pH-impedance monitoring. Issue 12 (1st July 2020) - Horton, Anthony; Posner, Shai; Sullivan, Brian; Cornejo, Jennifer; Davis, Andrea; Fields, Monika; McIntosh, Thasha; Gellad, Ziad; Shimpi, Rahul; Gyawali, C Prakash; Patel, Amit
Summary: Esophageal baseline impedance (BI) acquired during esophageal contraction (contractile segment impedance [CSI]) is proposed to improve BI accuracy in gastroesophageal reflux disease (GERD). We evaluated associations between CSI and conventional and novel GERD metrics. We analyzed high-resolution impedance manometry (HRIM) and ambulatory pH-impedance studies from 51 patients (58.6 ± 1.5 years; 26% F) with GERD symptoms studied off antisecretory therapy. Patients with achalasia or absent contractility were excluded. CSI (averaged across 10 swallows) and BI-HRIM (from the resting landmark phase) were acquired from the distal impedance sensors (distal sensor and 5 cm above the lower esophageal sphincter). Acid exposure time (AET) and mean nocturnal baseline impedance (MNBI) were calculated. Associations between CSI, BI-HRIM, MNBI, and AET were evaluated using correlation (Pearson) and receiver operating characteristic (ROC) analysis. Presenting symptoms included heartburn (67%), regurgitation (12%), cough (12%), and chest pain (10%). CSI-distal and CSI-5 each correlated with BI-HRIM, AET, and distal MNBI. Associations with AET were numerically stronger for CSI-distal (r = −0.46) and BI-HRIM-distal (r = −0.44) than CSI-5 (r = −0.33), BI-HRIM-5 (r = −0.28), or distal MNBI (r < −0.36). When compared to AET <4%, patients with AET >6% had significantly lower CSI-distal and BI-HRIM-distal values but not CSI-5, BI-HRIM-5, or MNBI. ROC areas under the curve for AET >6% were numerically higher for CSI-distal (0.81) than BI-HRIM-distal (0.77), distal MNBI (0.68–0.75), CSI-5 (0.68), or BI-HRIM-5 (0.68). CSI from HRIM studies inversely correlates with pathologic AET and has potential to augment the evaluation of GERD.